2018
DOI: 10.1002/chem.201705188
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Aza‐Bicyclononene Dienophiles for Rapid Fluorogenic Ligations

Abstract: Fluorogenic bioorthogonal reactions enable visualization of biomolecules under native conditions with excellent signal-to-noise ratio. Here, we present the design and synthesis of conformationally-strained aziridine-fused trans-cyclooctene (aza-TCO) dienophiles, which lead to the formation of fluorescent products in tetrazine ligations without the need for attachment of an extra fluorophore moiety. The presented aza-TCOs adopt the highly strained "half-chair" conformation, which was predicted computationally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 60 publications
0
16
0
1
Order By: Relevance
“…In addition, we and others have reported that reactions between 1,2,4,5‐tetrazines and particular dienophiles also lead to fluorescent products without the need for attachment of an extra fluorophore moiety . Despite successful application of this chemistry for bioimaging, we found that only the axially substituted hydroxy trans ‐cyclooctene and azabicyclononene dienophiles afforded fluorescent dihydropyridazine products. This limited scope of dienophiles suitable for fluorogenic labeling hampers broader utility of the methodology.…”
Section: Figurementioning
confidence: 92%
“…In addition, we and others have reported that reactions between 1,2,4,5‐tetrazines and particular dienophiles also lead to fluorescent products without the need for attachment of an extra fluorophore moiety . Despite successful application of this chemistry for bioimaging, we found that only the axially substituted hydroxy trans ‐cyclooctene and azabicyclononene dienophiles afforded fluorescent dihydropyridazine products. This limited scope of dienophiles suitable for fluorogenic labeling hampers broader utility of the methodology.…”
Section: Figurementioning
confidence: 92%
“…[24] The more recently described aza-TCO also displays rapid reactivity that is intermediate between s-TCO and d-TCO. [93] aza-TCO has been utilized in the formation of fluorescent products in tetrazine ligations that do not require attachment of an extra fluorophore moiety.…”
Section: Trans-cyclooctenes In Bioorthogonal Chemistrymentioning
confidence: 99%
“…Since our original description of the flow photoisomerization protocol, it has been employed by a number of groups for trans ‐cyclooctene synthesis with applications that include radiochemistry, cellular imaging, drug delivery and materials science . There have also been a number of modifications to the flow procedure that have been introduced.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…18 This result is in sharp contrast to related tetrazine motifs, which react vigorously with a variety of alkenes and alkynes. 12,13,[20][21][22][23][24][25][26][27][28] To expand upon the unique features of triazines, we aimed to synthesize and examine the reactivities of alternatively substituted rings. 1,2,4-Triazines react with dienophiles to form new bonds across C3 and C6.…”
mentioning
confidence: 99%